â€œPENGARUH IKLIM ORGANISASIONAL DAN GAYA KEPEMIMPINAN TERHADAP KEMAMPUAN DALAM MEMBERIKAN PELAYANAN DAN PONTIANAK KOTAâ€ - B31111022, TRI HAFSARI (Jurnal Manajemen Update, 2016)
The purpose of this study was to determine the influence of organizational climate and leadership style on the ability to provide services and their impact on employee performance. The data used in this study was obtained through the method of questionnaires. A total of 32 questionnaires submitted to the District Office employees Pontianak City in complete and can be processed. Data on though by using path analysis techniques using IBM SPSS 18.0 program. The results showed that organizational climate indirect effect on performance through service as an intervening variable. This is indicated by the value of the direct effect that is greater than the indirect effect (0.282> 0.047), and the leadership style directly affects the performance through service as an intervening variable. This is indicated by the value of the direct effect of which is smaller than the indirect effect (0.860<1.14). Keywords: climate organizational, leadership style, service and performance.